2012
DOI: 10.1155/2012/763057
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic Triplets and Dizygotic Twins following Transfer of Three Poor-Quality Cleavage Stage Embryos

Abstract: Background. Assisted reproductive technology has been linked to the increased incidence of monozygotic twinning. It is of clinical importance due to the increased risk of complications in multiple pregnancies in general and in monozygotic twins in particular. Case. A 29-year-old female, nulligravida underwent her first IVF cycle. Three poor-quality cleavage stage embryos were transferred resulting in monochorionic triamniotic triplets and dichorionic diamniotic twins. Selective embryo reduction was performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
(39 reference statements)
1
7
0
2
Order By: Relevance
“…In both of the present cases, the transferred embryos were of morphologically poor grade, similar to those in the report by Tal et al [ 20 ]. Two embryos were transferred, as the likelihood of pregnancy was considered to be extremely low for a single embryo transfer due to the embryo quality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In both of the present cases, the transferred embryos were of morphologically poor grade, similar to those in the report by Tal et al [ 20 ]. Two embryos were transferred, as the likelihood of pregnancy was considered to be extremely low for a single embryo transfer due to the embryo quality.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, numerous reports have implicated procedures, such as the micromanipulation of the zona pellucida, assisted embryo hatching, and ICSI [ 8 , 12 15 ], as factors related to MP. However, other studies suggest these factors may not be independent causes of MP [ 16 20 ]. Although extending the culture from the cleavage stage to the blastocyst stage may increase the incidence of MP [ 11 , 19 ], a recent study suggested that blastocyst transfers are not associated with an increased rate of monozygotic twin pregnancy when controlling for embryo cohort quality [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the fourth reported case of MCTA triplet following conventional IVF and blastocyst transfer without zona manipulation. [ 1 2 3 ] There are two reported cases following day 3 transfer[ 4 5 ] and two following FET[ 6 7 ] [ Table 1 ]. These cases reveal that with the exception of one patient of age 37, most patients were of young age, the average age being 28 years.…”
Section: Discussionmentioning
confidence: 99%
“…ЗБІРНИК НАУКОВИХ ПРАЦЬ АСОЦІАЦІЇ АКУШЕРІВ-ГІНЕКОЛОГІВ УКРАЇНИ Випуск 1 (41) 2018 ОТРИМАНІ РЕЗУЛЬТАТИ: Багатоплідними є приблизно 3% всіх вагітностей. Використання сучасних репродуктивних методик лікування неплідності призвело до значного підвищення кількості двієнь у всьому світі [44], навіть у разі пересадки одного ембріону [33,42]. За останні 25 років їх кількість збільшилась приблизно вдвічі [35].…”
unclassified
“…У жінок з БВ в 6 разів частіше виникають передчасні пологи і в 13 разів частіше пологи раніше 32 тижня, порівняно з вагітністю одним плодом [30]. Водночас, відомо, що частота та ступінь важкості акушерських і перинатальних ускладнень залежать від хоріальності та зиготності БВ, особливостей плацентації та початкового стану організму вагітної [1, 2,42]. Вищеозначені ускладнення частіше зустрічаються при монозиготних двійнях [34].…”
unclassified